2001
DOI: 10.1149/1.1400120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Amorphous 3Fe[sub 2]O[sub 3]⋅2P[sub 2]O[sub 5]⋅10H[sub 2]O and Its Electrode Performance in Lithium Batteries

Abstract: Amorphous 3Fe 2 O 3 •2P 2 O 5 •10H 2 O was prepared by oxidation of iron͑II͒ phosphate, obtained by spontaneous precipitation from iron͑II͒ and phosphate aqueous solutions, by heating in air at 100°C. The material was characterized by thermal analysis, Mo ¨ssbauer spectroscopy, X-ray powder diffraction, and scanning electron micrograph analysis. The material, tested as cathode in a nonaqueous lithium cell, exhibited a specific capacity of about 140 mAh g Ϫ1 at a current density of 25 mA g Ϫ1 . The utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…As mentioned above, it is obvious that such a performance is closely linked to the electrode surface area [23,24]. A similar behavior of good performance was observed by other authors [6][7][8], who explained it by the increase of the amorphous phase content as T c decreased. In spite of the higher surface value of the sample calcinated at 350°C, this latter shows an opposite trend, very likely because its structure being not well defined (cf.…”
Section: Tg Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…As mentioned above, it is obvious that such a performance is closely linked to the electrode surface area [23,24]. A similar behavior of good performance was observed by other authors [6][7][8], who explained it by the increase of the amorphous phase content as T c decreased. In spite of the higher surface value of the sample calcinated at 350°C, this latter shows an opposite trend, very likely because its structure being not well defined (cf.…”
Section: Tg Analysissupporting
confidence: 81%
“…It should be mentioned that the synthesis conditions used here give rise to a crystalline phase at temperatures well below those reported in the literature [6][7][8].…”
Section: Tg Analysismentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast to the crystalline ferric phosphate discussed above, amorphous ferric phosphate formed by the dehydration of the hydrate has a much higher capacity. Four different research groups published essentially identical data on this material [54,55,[96][97][98]. We found that the highest capacity was attained after complete dehydration at 350°C; at higher temperatures the electrochemically inactive verlinite phase begins to form.…”
Section: Other Iron Non-olivine Phosphatesmentioning
confidence: 59%
“…During the dilithiation process, the structure of LiFePO 4 is similar to FePO 4 and exhibits a little contraction in parameters a and b, a small increase in parameter c. The FePO 4 has also been proposed to be suitable cathode materials in lithium batteries, and lithium metal phosphates can be used as either cathode or anode in lithium batteries (Chen et al, 1996). With the conventional method of spontaneous precipitation of a solution containing Fe 3+ and PO 4+ at neutral or alkaline pHs, a wide series of lithium free iron phosphates have been prepared for (Prosini et al, 2001(Prosini et al, , 2002, Whittingham (Song et al, 2002a,b,c), Masquelier (Masquelier et al, 2002), Salah (Ait Salah et al, 2006) and Li (Li et al, 2006). Their results are in satisfactory agreement and inspirit later researches to improve its electrochemical performance as electrode materials.…”
Section: Introductionmentioning
confidence: 99%